Property of filler-loaded magnetic ferrite from plastic waste bottle used to treat municipal domestic sewage - Zhao, Ru-Jin (Environmental technology, 2018)
The present work investigates the properties of self-made magnetic filler from plastic waste bottle and explores a new technology approach of waste plastic resource utilization. The magnetic filler was prepared by air plasma modification and loading magnetic ferrite on the plastic strip from waste plastic bottle. The surface properties of magnetic filler were characterized by Atomic Force Microscope (AFM), contact angle system and Fourier Transform Infrared (FTIR). AFM images of original and modified plastic strip showed that low-temperature plasma treatment markedly increased the surface roughness of plastic strip. The mean roughness (Ra) of plastic strip rose from 1.116 to 5.024 nm. FTIR spectra indicated that a lot of polar oxygenic groups were introduced onto the surface of plastic by plasma modification. Modification by low-temperature plasma increased the hydrophilicity of plastic strip surface. When treatment time is 40 s, water contact angle of plastic strip surface reduced from 78.2° of original plastic strip to 25.3°. When used in bioreactor, magnetic filler had very favorable microenvironment for microorganism growth. Magnetic filler was more efficient for removing chemical oxygen demand (COD) and [Formula: see text] in sewage than nonmagnetic filler. The resource utilization of plastic wastes will become reality if the magnetic filler is applied widely